Respuesta :
Let's rewrite the second equation.
[tex] \frac{2}{3} p=q[/tex]
Multiplying both sides by [tex] \frac{3}{2} [/tex] gives us
[tex] \frac{3}{2} \cdot \frac{2}{3}p= \frac{3}{2}q\\ p= \frac{3}{2}q [/tex]
So the second equation is equivalent to the first equation. That means both equations represent the same proportional relationship. Cayley was correct.
[tex] \frac{2}{3} p=q[/tex]
Multiplying both sides by [tex] \frac{3}{2} [/tex] gives us
[tex] \frac{3}{2} \cdot \frac{2}{3}p= \frac{3}{2}q\\ p= \frac{3}{2}q [/tex]
So the second equation is equivalent to the first equation. That means both equations represent the same proportional relationship. Cayley was correct.
Answer:
cayley
Step-by-step explanation:
cuz i said so djsndkwndmdksnsnsnsnsnsns